MENGGAGAS KESEJAHTERAAN EKONOMI PEREMPUAN BERPENDAPATAN RENDAH MELALUI KOPERASI MITRA DHUAFA : STUDI KASUS KABUPATEN PIDIE JAYA - Benazir, Benazir (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
Mitra Dhuafa Cooperative (Komida) is a cooperative that provides financing for low-income women without requiring collateral in the loan application process. In its financing system, Komida targets women as beneficiaries because they are considered to have a greater responsibility in repaying loans according to the agreed time frame. The aim of this research is to improve the economic welfare of low-income women through Komida. Qualitative methods were chosen in this research, using grounded theory and narrative/historical approaches to systematically analyze the data and the various narratives listened to. The data collection process was carried out starting from reviewing and studying secondary data, interviews and observations of Komida members' business financing. Meanwhile, the research results show that overall, financing from Komida has had a real positive impact on poverty alleviation in Pidie Jaya. By supporting low-income groups through access to business capital, training and women's empowerment, Komida helps create a stronger foundation for inclusive and sustainable economic growth. This initiative not only improves the standard of living of individuals, but also strengthens the economic resilience of the community as a whole, contributes to poverty reduction, and supports local economic development in Pidie Jaya.